IMPLEMENTATION OF PSYCHOLOGICAL FIRST AID MODULE TO IMPROVE SKILLS IN PROVIDING PSYCHOLOGICAL SUPPORT PEERS AT STUDENTS - Hartanto, Agit Purwo; Harahap, Lukman; Nisa, Athia Tamyizatun (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
Psychological first Aid (PFA) is first aid for someone who experiences mild mental health disorders. Through mastery of PFA skills, students are expected to be able to provide support to peers who are experiencing mental health disorders. This study aims to test the effectiveness of the PFA Module to improve soft skills related to providing psychological support to peers in UIN Raden Mas Said Surakarta students. The design used in this study was Pre-experiment with 30 students consisting of various study programs at UIN Raden Mas Said Surakarta. After the analysis was carried out with the T-test, the results obtained were p < 0.05, meaning that the hypothesis was accepted. In conclusion, the PFA module is effective in improving soft skills in UIN Raden Mas Said students, especially in providing psychological support to peers.